The facile and efficient organocatalytic platform for accessing 1, 2, 4-selenadiazoles and thiadiazoles under aerobic conditions. Issue 10 (7th March 2018) - Putta, V.P. Rama Kishore; Gujjarappa, Raghuram; Vodnala, Nagaraju; Gupta, Richa; Pujar, Prasad P.; Malakar, Chandi C.
Graphical abstract: Highlights: First organocatalytic methods are devised towards 1, 2, 4-selenadiazoles and thiadiazoles. The methods exclude the need of metal-salts, toxic and stoichiometric oxidants as catalysts and reagents. Excellent yields and selectivity of the products were observed under operatioally easy conditions. Abstract: The first organocatalytic approach towards synthesis of rarely explored 1, 2, 4-selenadiazole and thiadiazole scaffolds have been devised using corresponding carboxamides as substrates. The transformations were realized using two distinct conditions in the presence of catalytic vitamin B3 or thiourea under aerobic conditions. Developed methods overcome the associated limitations of previous reported approaches and the desired products were obtained in high yields and selectivity without the formation of toxic side-products.